Knowledge and Practice Of Family Planning among Women of Reproductive Age in Okolobiri, Bayelsa State, Nigeria. - Oluchi Mkpae; Deborah Oboli; Tonte Nyingifa; Monica Anurika Gbuchie (International Journal of Medical Students, 2025)
BACKGROUND: The term “Family planning”is often used as a synonym for birth control. However, family planning does not only involve contraception but also considers planning a child’s birth for specific times (spacing the births a few years apart) and planning for a child when there are challenges in conception.Family planning services have the potential to build the quality of lives of people as it is important in the economic situation of the mother or family due to the financial demands in bringing up children.Family planning includes contraceptives, sexuality education and natural family planning. This study therefore seeks to understand the underlying factors and profer solutions through the promotion of relevant approach to family planning.